The Inheritance and Future Development Direction Prediction of Opera Culture Based on Cloud Communication under the Background of Big Data - Yufeng Yang (Journal of Sensors, 2022)
In the digital economy era, digital technologies such as cloud computing, big data, artificial intelligence, mobile Internet, and Internet of Things are becoming the new foundation of social operation and industry innovation. In order to achieve creative transformation and innovative development of traditional opera culture and art, there is a need to actively embrace the new digital technologies of the Internet. From the perspective of big data, according to the development status of Chinese opera art, this paper examines the limitations of traditional means to protect and develop opera art and puts forward the inheritance of opera culture and the prediction of future development direction based on cloud communication. This paper demonstrates the matrix system and inheritance development direction of Kunqu Opera culture to realize cloud communication. The main conclusions of this paper are as follows: firstly, promoting the overall digitalization of Kunqu Opera culture is the inevitable choice to realize the inheritance and development of Kunqu Opera; secondly, it is scientific and feasible to promote the overall digitalization and inheritance of Kunqu Opera culture. Thirdly, promoting the research and planning of cloud-spread opera should be promoted to become a national cultural strategy.